Prevenire la psicosi è davvero possibile? Alcune riflessioni - Masillo, Alice; Anzilotti, Carlo; Fiori Nastro, Paolo (Il sogno della farfalla, 2012)
Over the last decade the prevention paradigm has entered the world of psychiatry. Attention has been paid to the recognition of psychosis and early intervention. It is still among the most serious and debilitating of illnesses and quite a number of centres have been set up since the 80s with the task of identifying and offering early treatment for it. After years of therapeutic work, however, a diagnostic limit of the criteria used to identify the prodromic phase of psychosis has emerged. There is an evident lack in the description of subthreshold psychopathological phenomena which goes beyond a manifest and behavioural symptomatology, and research has now turned to identifying that core of psychotic vulnerability which is at a deeper and hidden level. The Authors believe that this nucleus of vulnerability is not to be understood as a neurologically-based fragility, which along with environmental factors gives rise to the pathology, but as a pathological nucleus that must be searched for in the non-conscious reality of the patient.